'I caught you!' Part 1: maturing separateness within the area of mutuality. Issue 1 (2nd January 2022) - Levi, Sheila
ABSTRACT: This paper, the first of two parts, aims to highlight the unique contribution that intensive psychoanalytic psychotherapy can make with complex cases where, in the absence of an engagement with another mind, self and ego development have been severely arrested. Intensive therapy with a boy aged four who was diagnosed with autism at the age of two is examined, to illustrate how the mind is both internally driven and relationally responsive. This work illustrates how the experience of analytic mutuality enables the development of the child's mental capacity for representation and symbolic thought, as well as relationality. Autistic encapsulation is understood as a psycho-physical protective reaction, rather than a psychodynamic defence mechanism. Clinical vignettes demonstrate how the therapist gradually emerges in the child's mind as an object to relate to and be made use of, alleviating arrested development and enabling the child to evolve from an almost mute, 'undrawn', confused and confusing child, into a latency boy with social, academic and behavioural skills.